Educação e plataformização: cenários, apropriações e embates - NUNES, Geanne Xavier (Universidade Federal do Oeste do Pará, 2024)
This article seeks to understand the phenomenon of the platformization of education through a review study focused on Brazilian bibliographic production on the subject. The results of the analysis process of the works in the sample were organized according to analytical-descriptive categories related to: a) scenarios and concepts; b) uses and appropriations; c) challenges and implications. In terms of results, it points out that, given the trend of expanding platformization in education, it is essential for professionals and researchers to develop a critical and systematic approach in order to counter the hegemony and interests of technology industries regarding the production of discourses and digital systems linked to this scenario.